Pemberdayaan Keluarga Melalui Kewiraswastaan - Farah Chalida Hanoum; Ria Kusumaningrum (Da'watuna: Journal of Communication and Islamic Broadcasting, 2021)
The field of entrepreneurship and family business consist of separate and distinct but overlapping domains. The intersection of the two domains provides a uniqe perspective from which to examine six strategic management issues : leadership, culture, board of directors, life cycles, strategic management process, ethics and values.